The level of importance of food labels on food products - Zul Ariff Abdul Latiff; An Nur Nabila Ismail; Mohammad Amizi Ayob (2016)
The purpose of the research was to examine the level of importance of food labels on food products towards customer in Kelantan. From the research, the researcher has collected primary data and the secondary data that related to the problems of research. In this study, quantitative approach was used and 200 respondents have been selected from Kota Bharu, Kelantan. The questionnaires were distributed to the respondents to gather the necessary information. After all data has been collected, the researcher analyzes data using SPSS and interpreted in the diagrams view. Based on the study that has been conducted, the result shows that the most significant factor that can use to examine the level of importance of food labels on food products are awareness and knowledge, attitude toward food level, subjective norm, perceived behaviour control and intention.